2015
DOI: 10.1038/nrcardio.2015.38
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-mediated mechanisms of the cellular stress response in atherosclerosis

Abstract: | Atherosclerosis is characterised by the accumulation of lipid-laden macrophages in atherosclerotic lesions and occurs preferentially at arterial branching points, which are prone to inflammation during hyperlipidaemic stress. The increased susceptibility at branching sites of arteries is attributable to poor adaptation of arterial endothelial cells to disturbed blood flow. In the past 5 years, several studies have provided mechanistic insights into the regulatory roles of microRNAs (miRNAs) in inflammatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 192 publications
(241 reference statements)
1
70
0
1
Order By: Relevance
“…Here, we found that fluorescently labeled exosomes were internalized into endothelial cells (see Figure E3), where they could be implicated in a myriad of important processes (39)(40)(41)(42)(43)(44). Based on the selectivity of miRNA loading into extracellular vesicles (EV) and their stability (45), potential differences in miRNA exosomal cargo were identified, and were compatible with previous work implicating exosomal miRNAs not only in angiogenesis and other vascular phenomena (46,47), while also suggesting the possibility that exosomes may provide therapeutic opportunities (48). We recently assessed the biomarker capabilities of plasma miRNAs (19), and our findings support the driving assumption that a cluster of circulating miRNAs may reliably discern between children with ED and children with NEF.…”
Section: Discussionsupporting
confidence: 69%
“…Here, we found that fluorescently labeled exosomes were internalized into endothelial cells (see Figure E3), where they could be implicated in a myriad of important processes (39)(40)(41)(42)(43)(44). Based on the selectivity of miRNA loading into extracellular vesicles (EV) and their stability (45), potential differences in miRNA exosomal cargo were identified, and were compatible with previous work implicating exosomal miRNAs not only in angiogenesis and other vascular phenomena (46,47), while also suggesting the possibility that exosomes may provide therapeutic opportunities (48). We recently assessed the biomarker capabilities of plasma miRNAs (19), and our findings support the driving assumption that a cluster of circulating miRNAs may reliably discern between children with ED and children with NEF.…”
Section: Discussionsupporting
confidence: 69%
“…47,48 A contribution of different eRNA species is emerging as critical mediators of these mechanisms that control (ischemic) cardiovascular disease. As recent reviews have specifically concentrated on various aspects of miRNAs in this context, [12][13][14][15] these issues will not be dealt with here in detail.…”
Section: Erna In Cardiovascular Diseasesmentioning
confidence: 99%
“…It should be noted, however, that in many cases, we currently do not yet understand whether certain types of eRNA, structural prerequisites, or specific nucleotide sequences of the RNA are required to exert their functions, which is an uncertainty embodied by the rather unspecific term eRNA. The function of miRNAs in this context has been reviewed elsewhere [12][13][14][15] and will not be discussed in detail.…”
Section: Extracellular Nucleic Acidsmentioning
confidence: 99%
“…Cardiovascular diseases are among them. Because there are already thorough reviews that summarize current knowledge about miRs implicated in atherosclerosis susceptibility, development, and progression [81][82][83][84][85][86][87][88] , we will focus on the part of atherosclerosis pathology where different miRs could potentially alter vascular physiology by the direct or indirect regulation of CXCL16 gene expression.…”
Section: Rs3744700 (T/g)mentioning
confidence: 99%